Liquefaction hazard zonation mapping of the Saitama City, Japan (Journal of Nepal Geological Society, 2010)
Liquefaction hazard zonation mapping of the Saitama City targeted on the Kanto Plain NW Edge Fault is described in this paper. The study involves the geotechnical properties of the alluvial soil of the city including Standard Penetration Test (SPT), shear wave velocity and other geological data analysis. The city being highly urbanized is situated on the soft soil (alluvial deposits) at the proximity of an active seismic fault that has increased the possibility of liquefaction hazard in the area. Kanto Plain NW Edge Fault is an active fault that lies very near to the Saitama City having the estimated possible earthquake magnitude of 7.4. The possible peak horizontal ground acceleration (amax) from this earthquake is calculated as from 0.15 g to 0.30 g. By considering all possible acceleration values the liquefaction potential maps were prepared and presented in this paper. Additionally, the shear wave velocity is very low and amplification ratio is very high at the marshy deposit but it has comparatively high velocity and low amplification ratio at the marine loam deposit area of the Omiya Plateau. In this paper the liquefaction potential of the area is expressed in terms of liquefaction potential index (PL). The PL value for the clayey silt deposit in the marshy area with shallow water table is very high. In addition, the PL value in the marine loam deposit of the Omiya Plateau is less which indicates that loam deposit has less liquefaction potential than marshy deposit. The map obtained from this study was validated with the field condition of the study area. Hence, it is expected that this study will assist in characterizing the seismic hazards and its mitigation and will provide valuable information for urban planning in the study area in future.